Optimalisasi Pembelajaran melalui Manajemen Sarana dan Prasarana : Suatu Tinjauan terhadap Manajemen Berbasis Sekolah - Ivon Abdullah Nabil; Ahmad Aprindo Hengky Setiawan; Nor Lathifatur Rohmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to descriptively explore the role of facility and infrastructure management in enhancing learning effectiveness at the elementary school level, viewed from the perspective of School-Based Management (SBM). SBM is an educational management approach that emphasizes school autonomy in planning, implementing, and evaluating all learning activities as well as managing available resources, including educational facilities and infrastructure.This research employs a descriptive qualitative approach, with data collection techniques including in-depth interviews, direct field observations, and document analysis. The subjects of this study include the principal, teachers, and administrative staff responsible for managing school facilities and infrastructure at a selected public elementary school. The main focus is to examine how management processes are carried out and how these contribute to the continuity and quality of the learning process.The findings indicate that the management of facilities and infrastructure is conducted systematically through four main stages: needs planning based on situational analysis, procurement through collaboration with school committees or third parties, optimal utilization of facilities to support learning activities, and regular maintenance to ensure continued functionality. This process involves active participation from various stakeholders, both internal and external to the school, and is guided by the principles of transparency, accountability, and efficiency .Adequate availability of facilities and effective management were shown to create a conducive learning environment, increase student motivation, and support teachers in delivering lessons effectively. Furthermore, well-maintained facilities contribute to fostering a culture of discipline and a sense of responsibility among students. This study recommends enhancing the managerial capacity of principals and staff in facility management and strengthening cooperation between the school, the school committee, and the wider community to support the delivery of quality and sustainable education